Survey geologi P.L.T.M. Bengkayang - Radja, Vincent T. (Publikasi - Lembaga Masalah Ketenagaan ; 01-Geol-75., 1975)
Geological survey of the Bengkayang Micro Hydro Electric Power Plant, West Kalimantan.